INVESTIGATING COLLEGE STUDENTS’ PERCEPTIONS ON QUIZIZZ AS AN EFFECTIVE LEARNING TOOL IN THE ENGLISH FOR YOUNG LEARNERS (EYL) CLASS IN THE ENGLISH DEPARTMENT - Wilda Widiana; Silih Warni (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Technology integration in education, especially in language learning, has become increasingly essential. This study investigates college students’ perceptions regarding using Quizizz as a practical learning tool in the English for Young Learners (EYL) course. Employing a quantitative survey method, data were collected from 30 students in the English Department at a university in Jakarta using a five-point Likert scale questionnaire. The survey assessed students’ perceptions across several aspects, including ease of use, effectiveness in enhancing understanding, and the ability to increase engagement and motivation. The findings reveal that students generally perceive Quizizz positively, appreciating its user-friendly interface, interactive features, and real-time feedback. This contributes to improved confidence and a more enjoyable learning experience. Furthermore, students reported that Quizizz supports their comprehension of EYL material and fosters greater motivation to participate in class activities. These results suggest that Quizizz is a valuable digital tool for educators aiming to enhance the quality of language learning. However, the study also acknowledges the need for further research involving larger and more diverse samples and longitudinal studies to examine the long-term impact of Quizizz on students’ academic performance.